2003
DOI: 10.1097/00005537-200309000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes in the Management of Inverted Papilloma: An Analysis of 160 Cases

Abstract: We present the largest personal series of cases of inverted papilloma to date. Our data suggest that conservative approaches, especially endoscopic removal, can be performed on selected lesions with recurrence rates that are comparable to those of more aggressive techniques. Those inverted papillomas that recur after treatment may represent a subset of lesions with an inherent aggressiveness, for which optimal treatment has yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
179
2
15

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(203 citation statements)
references
References 36 publications
7
179
2
15
Order By: Relevance
“…Evolution to SCC has been reported in 1% to 53% of IP cases. 8,9 Therefore, a thorough removal of all diseased mucosa, a meticulous histological examination of the entire specimen, and the postoperative long-term follow-up of these patients are recommended. Although multiple studies have been performed on IP, neither the etiology of IP nor the factors responsible for malignant transformation are fully elucidated to date.…”
Section: Discussionmentioning
confidence: 99%
“…Evolution to SCC has been reported in 1% to 53% of IP cases. 8,9 Therefore, a thorough removal of all diseased mucosa, a meticulous histological examination of the entire specimen, and the postoperative long-term follow-up of these patients are recommended. Although multiple studies have been performed on IP, neither the etiology of IP nor the factors responsible for malignant transformation are fully elucidated to date.…”
Section: Discussionmentioning
confidence: 99%
“…It is a rare sinonasal tumor comprising only 0.5-4% of all nasal tumors [1]. Although this tumor is benign in nature, it exhibits the characteristics of local invasiveness, recurrence, and malignant transformation [2][3][4][5].The incidence of malignant change in individual series of inverted papillomas ranges from 2 to 27% [6]. Recently, it was reported that there is a clear relationship between paranasal IP and squamous cell carcinoma (SCC), and that nearly 10% of inverted papillomas are associated with SCC [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is more common in men and usually presents in the fifth and sixth decades of life [10]. Unilateral disease and unilateral nasal obstruction is the most common presenting feature [11,12] but, as demonstrated in this article, bilateral disease does occur with reported rates of 2-7% [1,6,7]. The etiology of this multicentric appearance has yet to be fully understood.…”
Section: Discussionmentioning
confidence: 95%
“…CT scanning is the initial modality of choice to evaluate the extent of disease [16]. Bony erosion can be present with inverted papillomas in as much as 44% [6] but raises concern over potential malignant change. More recently magnetic resonance imaging has been used to aid in the assessment and guide surgery as it can accurately distinguish between retained secretions and the soft tissue of a tumor [6,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation